A Study of the SP Geophysical Technique in a Campus Setting - Leitch, A.; Boone, C. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2007)
Abstract The self potential (SP) method is a simple and inexpensive geophysical surveying technique, which involves measuring electrical potentials on the surface due to charge separations in the subsurface. These charge separations can arise from a number of different physical and electrochemical processes, and hence interpretations tend to be qualitative. Small anomalies are typically neglected as transient, inexplicable, or uninteresting. In contrast, large negative anomalies associated with ore bodies are noted for their constancy. In this study, an area on the campus of Memorial University was repeatedly surveyed in order to determine which natural and anthropogenic features generated SP anomalies, and whether these anomalies were constant or transient. We found anomalies associated with a building, a buried metallic pipe, trees, and subtler ground variations. The locations of anomalies, both large and small, were notably unvarying over a period of days and weeks. The building always generated a significant negative anomaly, but the sign of other anomalies (including that associated with the pipe) and the magnitude of all anomalies varied with time. In a second area dominated by a shallow sewer pipe, SP data allowed modeling of the burial depth and charge distribution of the pipe. Our results show that SP can be a useful and reliable method for shallow ground surveys, but that the time-varying nature of both sign and magnitude of small to moderate anomalies should be taken into account in data collection and interpretation.